The art of cyber security : a practical guide to winning the war on cyber crime - Hibberd, Gary (IT Governance Publishing, 2022)
This book is about cyber security. In Part 1, the author discusses his thoughts on the cyber security industry and how those that operate within it should approach their role with the mindset of an artist. Part 2 explores the work of Sun Tzu's The Art of War.